Pandangan Guru Sekolah Dasar terhadap Menu Pelatihan Mandiri pada Platform Merdeka Mengajar (PMM) - Kartono, Kartono; Johan, Gio Mohamad (AS-SABIQUN, 2024)
The existence of the independent teaching platform (PMM) is a means that helps teachers obtain inspiration, references and additional information in implementing the independent curriculum in each educational unit. This is the background to the research, namely regarding teachers' perceptions of the independent training features provided by the independent teaching platform (PMM). The objectives of this research are (1) to describe the understanding of the independent training features provided by the independent teaching platform (PMM) and (2) teacher assessments of the independent training features provided by the independent teaching platform (PMM). This research method is descriptive with a qualitative approach. Data collection uses several data collection techniques and instruments. The data analysis technique goes through the flow of data collection, data reduction, data presentation, and drawing conclusions. The results obtained in the form of an understanding of independent training for teachers and an assessment of the features provided by the research sample obtained good results. The conclusion of this research is that the independent training feature on the independent teaching platform (PMM) can be an alternative means of independent learning for teachers to develop themselves.